Scrolling and Stress: Exploring Internet Usage for Social Media and Psychological Distress in Young Adults - P C Pradeep Kumar; M Kishor; Archana Anthony Raj; M. Murugappan; Dhanabal S. Palaniswamy (Annals of Indian Psychiatry)
Background: Internet usage is increasing significantly among young adults for various purposes. Understanding the extent of their social media engagement is crucial. This study aims to explore how much young adults use the Internet for social media and its link to psychological distress. Methods: The study included 423 UG and PG students from two private colleges in Ooty, Tamil Nadu. They were selected using a purposive sampling technique. An online survey collected data through a sociodemographic data sheet, the Internet Use Scale, and the Kessler 10 Psychological Distress Scale. Results: The findings revealed that 26% (n = 111) of students excessively use the Internet for social media activities. More males (56.76%) than females (43.24%) use this excessively. Around 23% of these heavy users have four or more social media accounts. Instagram is the most popular platform (32%), followed by combinations such as Instagram, Snapchat, and YouTube (28%), and Instagram paired with YouTube (20%). Excessive Internet users (P < 0.001) spend an average of 3.57 h on social media, while nonexcessive users spend 2.51 h. Over half of the excessive users had psychological distress (P < 0.001). Significant positive correlations were found between average social media usage hours, Internet use score, and psychological distress (P < 0.001). Conclusion: Internet usage for social media activity is rising among students, and using multiple social media accounts and excessive use are associated with psychological distress.